A 5G beam-steering microstrip array antenna using both-sided microwave integrated circuit technology - Hossain, Md. Farhad; Das, Debprosad; Hossain, Md. Azad (Institute of Advanced Engineering and Science, 2024)
In this paper a beam steering 2×2 microstrip array antenna is proposed and simulated for the 5G sub-6 GHz frequency band. The array antenna is designed at the resonant frequency of 3.5 GHz. The antenna has four patches excited by two microstrip lines. Microstrip lines on top of teflon substrate of 0.8 mm height and slot line in the ground plane makes a hybrid junction. The design uses both sided microwave integrated circuit (MIC) to feed signal to the patch elements. This designed array antenna has the beam steering capability of maximum -17º to +17º while keeping the side lobe gain below 10 dB. The simulation results show that the array antenna is designed through good input impedance matching. The antenna has a return loss of -43 dB at center frequency 3.5 GHz. The results also show that the array antenna has a high gain of 12.57 dBi and directivity of 25.11 dB. The maximum gain of this antenna is 24.1 dB at -17º and +17º. The proposed work is simulated on keysight technologies advanced designed system (ADS).